Serving LGBTQ teens : a practical guide for librarians - Houde, Lisa (Practical guides for librarians, 2018)
This book offers the librarian a practical guide to library service to LGBTQ teens - from collection development, understanding terminology, dealing with censorship issues, programming and outreach, readers' advisory, and even to creating welcoming displays, librarians will find the tools they need to offer exceptional services for LGBTQ teens.